2022
DOI: 10.1038/s41390-022-02162-0
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics in pediatric lower respiratory tract infections and sepsis: a literature review

Abstract: Lower respiratory tract infections (LRTIs) are a leading cause of morbidity and mortality in children. The ability of healthcare providers to diagnose and prognose LRTIs in the pediatric population remains a challenge, as children can present with similar clinical features regardless of the underlying pathogen or ultimate severity. Metabolomics, the large-scale analysis of metabolites and metabolic pathways offers new tools and insights that may aid in diagnosing and predicting the outcomes of LRTIs in childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Wildman et al 24 . reviewed the above studies at the metabolic level in children with sepsis and found that three metabolites (3‐hydroxybutyrate, glucose, and acetone) overlapped in these findings, suggesting that these three metabolites may be promising biomarkers targets for further clinical validation.…”
Section: Biomarkers Screened By Metabolomicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Wildman et al 24 . reviewed the above studies at the metabolic level in children with sepsis and found that three metabolites (3‐hydroxybutyrate, glucose, and acetone) overlapped in these findings, suggesting that these three metabolites may be promising biomarkers targets for further clinical validation.…”
Section: Biomarkers Screened By Metabolomicsmentioning
confidence: 99%
“…Several studies have previously summarized the progress of research on sepsis markers in children. 3,[18][19][20][21][22][23][24][25] In this study, we reviewed the research progress about pediatric sepsis markers from different levels according to the omics tools used for biomarker identification. Since the neonatal immune response against sepsis is different from that of children, sepsis biomarkers screened by using neonatal samples were not included in this review.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations